Four essays on systemic risk estimation - Siuda, Vojtěch; Málek, Jiří, 1953-; Aruga, Kentaka; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
This dissertation consists of four articles that focus on estimating systemic risk in the banking sector. The articles and the approaches and analyses presented in them are predominantly practical and empirical, while providing the necessary theoretical motivation for the research topics. The first article introduces a framework for assessing corporate exposures, considering industry-specific factors and the propagation of economic shocks across sectors. The second article examines systemic risks of sovereign exposures, including an approach to estimating and predicting credit risk of government bonds. The third article addresses the transition to a low-carbon economy and its impact on the financial sector, along with potential threats to its stability. The fourth article presents an approach to modeling risk-weighted assets of banks under different economic scenarios and limitations of their cyclical behavior. The approaches presented in each article bring some degree of novelty, whether in the form of previously unpublished analyses and approaches, the application of existing models in new areas, or the utilization of new data sources. Each article also emphasizes the mitigation of potential systemic risks through appropriate macroprudential policies, alongside the theoretical and empirical components.
Vedoucí práce: Jiří Málek
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations